The transition of finance in Japan and the United States : - Cargill, Thomas F. (Hoover Institution Press, 1988)
Financial liberalization since the mid-1970s has increased the role of competitive forces in both the Japanese and U.S. financial systems. This article assesses the role of competition as an explicit objective of the financial liberalization process and, in particular, focuses on recent arguments made about the relative degree of competition between the two financial systems. The article argues that enhanced competition has never been a major objective of financial reform and that the U.S. financial system has been and remains more competitive even after extensive liberalization in Japan.